Comprehensive subspecies identification of 175 nontuberculous mycobacteria species based on 7547 genomic profiles. Issue 1 (1st January 2019) - Matsumoto, Yuki; Kinjo, Takeshi; Motooka, Daisuke; Nabeya, Daijiro; Jung, Nicolas; Uechi, Kohei; Horii, Toshihiro; Iida, Tetsuya; Fujita, Jiro; Nakamura, Shota
ABSTRACT: The prevalence of nontuberculous mycobacteria (NTM) pulmonary diseases has been increasing worldwide. NTM consist of approximately 200 species and distinguishing between them at the subspecies level is critical to treatment. In this study, we sequenced 63 NTM genomes, 27 of which were newly determined, by hybrid assembly using sequencers from Illumina and Oxford Nanopore Technologies (ONT). This analysis expanded the available genomic data to 175 NTM species and redefined their subgenus classification. We also developed a novel multi-locus sequence typing (MLST) database based on 184 genes from 7547 assemblies and an identification software, mlstverse, which can also be used for detecting other bacteria given a suitable MLST database. This method showed the highest sensitivity and specificity amongst conventional methods and demonstrated the capacity for rapid detection of NTM, 10 min of sequencing of the ONT MinION being sufficient. Application of this methodology could improve disease epidemiology and increase the cure rates of NTM diseases.